LOS DERECHOS HUMANOS, FRENTE AL CONFLICTO DEL MEDIO ORIENTE Y AL ESTADO ISLÁMICO (2016)
This paper refers to the violation of human rights in the Islamic state. It starts from the analysis of the socio-cultural and religious paradigms that show the people who belong to the Islamic jihad and that shows today some concern in the world given that these radical leaders have organized religious movement that pretends to organize the Islamic state to extend westward the guidelines of Islam; this group has already beheaded mercilessly journalists and Americans, French and English. Given this sample of religious and political fanaticism that violates human rights, the countries involved have decided to address them through targeted bombings that weaken its military and economic infrastructure.